Peran kader Ranting 'Aisyiyah Cabang Kota Yogyakarta dalam pemberdayaan masyarakat di bidang kesehatan - Hidayati, Ririn Wahyu; Mahmudah, Nurul (Jurnal Kebidanan, 2020)
Health cadres have a role to assist the government in improving community health status, reducing MMR and IMR. One of his roles is to become a Posyandu cadre in Aisyiyah. But in reality, cadres have a dual role. Therefore, the researcher intends to find out how far the participation of Health cadres is in Branch Aisyiyah, Yogyakarta City Branch. This research is a qualitative study and was conducted at the Branch of ‘Aisyiyah Yogyakarta City Branch in 2017. The number of participants was taken to have a saturated answer from the cadre of isy Aisyiyah. Test analysis with content analysis. The results obtained that the cadres ‘Aisyiyah collaborated with educational institutions both ‘Aisyiyah or Muhammadiyah to provide health education, health checks and treatment. Health related activities are carried out both in the activities of recitation, social gathering, study or routine meetings of warga Aisyiyah residents. Other programs that are running are TB Knocking, assistance in taking medicine, Posyandu Elderly Sakinah, and early detection of non-communicable diseases. ‘Aisyiyah cadres play a role in mutual cooperation" from, for and by the community ". The number of cadres and the age of keder ‘Aisyiyah is not a barrier to their performance. Complementarity and cooperation are the keys to the implementation of work programs in accordance with the aim of improving the level of public health. Young cadres as implementers, senior cadres as advisors. Based on the results of the study it can be concluded that Aisyiyah cadres play an active role to improve public health despite having a dual role.